Periodontal Health Status and Microbiological Analysis of Orthodontic Patient in Dhaka Bangladesh (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Aim: The aim of the study was to determine the level of bacteria in dental plaque associated with fixed orthodontic appliances.Materials and Methods: This longitudinal observational study was done during April’2014 to September’2014 in the Department of Microbiology, Primeasia University, Banani, Dhaka. The 100 samples were collected purposively from the Department of Orthodontics, University Dental College and Hospital, Dhaka and reported private Orthodontic clinic of Bangladesh. The microbiological test was done in the Department of Microbiology, Primeasia University, Banani, Dhaka.Results: The study result showed, there were significantly increased plaque accumulation as well as microorganisms in patient who wear fixed orthodontic appliances than normal subjects. Most of the organisms were streptococcus and most organisms were sensitive to antibiotic except eromycin, sensitive to paste (triclosan and fluoride) but resistant to mouth wash.Conclusion: The components of fixed appliance can hamper proper oral hygiene maintenance increases the chance of accumulation of plaque that lead to caries. So appropriate tooth brush with proper paste can inhibit microbial colonization on tooth surfaces.Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.17-23